2020
DOI: 10.1177/0300060520925653
|View full text |Cite
|
Sign up to set email alerts
|

ETView VivaSight single lumen vs. conventional intubation in simulated studies: a systematic review and meta-analysis

Abstract: Objective The ETView VivaSight single lumen airway tube (ETView) is a tracheal tube incorporating a video camera. We carried out a meta-analysis of previous simulation studies by inexperienced personnel to determine if the ETView could improve the success rate of first-attempt intubation. Methods We collected data from randomized controlled trials comparing the use of the ETView VivaSight single lumen versus a conventional endotracheal tube in a simulated manikin or cadaver study. Results Eleven studies (558 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…It has been compared to conventional laryngoscopy in simulated manikin or cadaver studies. 3 Clinical studies found improved visualization but prolonged intubation times compared with videolaryngoscopy in patients with expected difficult airways. 4 In our reported case, the combination of two methods-VivaSight SL and videolaryngoscopy-facilitated successful tracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been compared to conventional laryngoscopy in simulated manikin or cadaver studies. 3 Clinical studies found improved visualization but prolonged intubation times compared with videolaryngoscopy in patients with expected difficult airways. 4 In our reported case, the combination of two methods-VivaSight SL and videolaryngoscopy-facilitated successful tracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been compared to conventional laryngoscopy in simulated manikin or cadaver studies. 3 Clinical studies found improved visualization but prolonged intubation times compared with videolaryngoscopy in patients with expected difficult airways. 4…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VivaSight™ performed better, with a higher success rate, shorter insertion time and better laryngeal view, in difficult airways. [51] Its use during cardiopulmonary resuscitation was tested in a simulation study. Its effectiveness at the first attempt was 100%, with a median time to intubate of 25.5 seconds (IQR; 24-28.5 seconds).…”
Section: Endotracheal Tubes and Conductorsmentioning
confidence: 99%